The relationship between board composition and nonprofit organizational performance, the case of UK charity - Li, Xiaoran (2018)
This study examines the impact of board composition on nonprofit organizational performance by using the data collected from UK charities, aiming to provide evidence on the relationship between specific characteristics of board composition and nonprofit organizational efficiency. Specifically, board size, existence of audit committees, gender diversity and educational level diversity are used as factors to affect performance of UK charity. Agency theory, resource dependency theory and group/decision process theory are employed as theoretical framework to explain the rationale of such association and contribute to the recognition and understanding of the effect of board composition on nonprofit organizational performance. Fundraising expense ratio and program expense ratio are employed as proxies to nonprofit organizational efficiency. Results show that certain characteristics of board composition are statistically significantly related to UK charity performance.